Validity of aerosolization detection with an air quality indicator in noncontact tonometry using corneal phantoms - Ibinson, Jonathan T.; Yousefi, Atieh; Roberts, Cynthia J.; Reilly, Matthew A. (Frontiers in Ophthalmology, 2022)
Purpose: To evaluate the accuracy of aerosol concentrations reported by an air quality indicator (AQI) following an air puff from a noncontact tonometer using non-aerosolizing corneal phantoms. Methods: Three rubber corneal phantoms of different stiffnesses were used to represent varying intraocular pressure (IOP) values. No liquid components and therefore no aerosol-generating potential was present. Reported concentrations of particulate matter (PM) having diameter less than 2.5 and 10µm, respectively PM2.5 and PM10, were recorded using an AQI before and during an air puff generated using noncontact tonometry. The effects of covariates IOP and sensor location on changes to air quality measurements from the baseline were evaluated using analysis of variance. Monte Carlo simulations were used to determine the likelihood of observing published trends by chance. The statistical significance threshold was p<0.05. Results: No correlations were found between PM2.5 and IOP or location. Reported concentrations of PM10 depended significantly on both IOP (p=0.0241) and location (p=0.0167). Monte Carlo simulations suggest the likelihood of finding a spurious positive correlation between IOP and PM at the upper same location are 53% and 92% for PM2.5 and PM10, respectively, indicating the AQI has systematic bias resulting from non-aerosol sources. Conclusions: We were able to reproduce the published correlation between reported aerosol concentration and IOP in non-contact tonometry using dry rubber phantoms in place of living corneas with tear films. In this study, we demonstrated that published correlations linking NCT to tear film aerosolization were artifacts of the measurement technique.